Analysis of Business Development Strategy Agrowisata Bhumi Merapi with Business Model Canvas Approach - Khoirul Aziz Husyairi; Wega Linanda Pratomo; Raden Halerefky Adam Purboseputro (Jurnal Sains Indonesia, 2020)
This study aims to analyze the business development strategy of Bhumi Merapi Agro-tourism by using the Business Model Canvas approach. The research method used is descriptive qualitative research. Data collection techniques used were in-depth interviews and literature studies. The analysis was performed using Business Model Canvas and SWOT Analysis. The results obtained in the form of a nine-block image on the company's current business model canvas and the formulation of the development in the form of an image of nine upcoming business model canvas. The development strategy is carried out by expanding the customer segment, adding partners, maximizing the company's social media channels, and increasing physical resources with a vehicle that supports the expansion of the customer segment.